Wavelet Theory and Its Applications - Radhakrishnan, Sudhakar (IntechOpen, 2018)
This book is intended to attract the attention of practitioners and researchers in the academia and industry interested in challenging paradigms of wavelets and its application with an emphasis on the recent technological developments. All the chapters are well demonstrated by various researchers around the world covering the field of mathematics and applied engineering. This book highlights the current research in the usage of wavelets in different areas such as biomedical analysis, fringe-pattern analysis, image applications, network data transfer applications, and optical measurement techniques. The entire work available in the book is mainly focusing on researchers who can do quality research in the area of the usage of wavelets in related fields. Each chapter is an independent research, which will definitely motivate the young researchers to ponder on. These 12 chapters available in four sections will be an eye opener for all who are doing systematic research in these fields.